Indonesian Student Perception in Digital Payment - Aldilla Iradianty; Bayu Rima Aditya (Universitas Pendidikan Nasional, 2020)
The trend of using digital payment in Indonesia is increasing every year. Most people have been felt the benefit of Digital Payment service. This research provide perspective about awareness, perceptions and preferences of students in Indonesia towards digital payment-based payment system. This quantitative research involved 104 students from various universities in Indonesia. The information collected by a questionnaire and was analyzed by descriptive statistical techniques. The result of this study indicate that the awareness of students in Indonesia about digital payment services is very high. The convenience of using this service, the availability of services, discounts and reward points are the main factors that influence them in choosing digital payment service. This research also show that the majority of students prefer to continue using digital payment service. The results of this study can be useful for digital payment service provider in order to increase service satisfaction.